(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2019)
The transformations in contemporary media ecosystem require a regulatory balance between access to online content services, consumer protection and competitiveness to be achieved. As part of the Digital Single Market strategy, the European Commission revised in November 2018 the existing Audiovisual Media Services Directive as a media regulatory framework for the 21st century in order to adopt fairer regulatory rules for the entire audiovisual sector in the European Union. The aim of the proposed paper is to determine the extent of the applicability of the criteria and the standards outlined in the Council of Europe’s Recommendation on a New Notion of the Media (2011) in the contemporary communication environment in Bulgaria. Qantitative and qualitative social surveys were conducted in December 2018/February 2019 among journalism students, media practitioners and media experts in order to answer the main research question to what extent the global challenges of ICTs have impacted the national media ecosystem, which encompasses the interaction of all actors and factors for allowing the media to function and to fulfil their role in society. The results of the surveys outline the basis of discussion and analysis of the media trends in the country in multi-layered aspects.